The Translation of Wali/ Auliya in English Al-Quran: Comparative Study on Yusuf Ali and Muhsin Khan - Doamad Tastier (The Progress: Journal of Language and Ethnicity, 2022)
Abstact Polysemy has problematic issues in the study of linguistics since one word can have many meanings. It depends on the context of many things. Moreover in translation. The accurate of choosing the equivalence in target language is much more difficult. This research is an attempt to analyze two translation works. The first work is The Holy Qur’an with English Translation and Commentaries by Yusuf Ali, and the second is Interpretation of The Meanings of Noble Qur’an: A Summerized Version of at-Tabari, al-Qurtubi and Ibn Kathir with Comments from Sahih al-Bukhari by Muhsin Khan and Taqiudin Al Hilali. This research is qualitative research. This research finds that the word wali/auliya and its derivations are translated into various ways. In some places they are translated into the same words and in another place they are translated differently. However, Muhsin Khan and Hilali mostly translate this word into the same word, wali/auliya with explanation following in the bracket. Keywords: polysemy, wali/auliya, translation.